The Lateral Hypothalamic Area Controls Paradoxical (REM) Sleep by Means of Descending Projections to Brainstem GABAergic Neurons - Clément, Olivier (J Neurosci, 2012)
It has recently been shown that the ventrolateral part of the periaqueductal gray (VLPAG) and the adjacent dorsal deep mesencephalic nucleus (dDpMe) contain GABAergic neurons gating paradoxical sleep (PS) onset by means of their projection to the glutamatergic PS-on neurons of the sublaterodorsal tegmental nucleus (SLD). To determine the mechanisms responsible for the cessation of activity of these GABAergic PS-off neurons at the onset and during PS, we combined the immunostaining of c-FOS, a marker of neuronal activation, with cholera toxin b subunit (CTb) retrograde tracing from the VLPAG/dDpMe in three groups of rats (control, PS deprived, and PS hypersomniac). We found that the lateral hypothalamic area (LH) is the only brain structure containing a very large number of neurons activated during PS hypersomnia and projecting to the VLPAG/dDpMe. We further demonstrated that 44% of these neurons express the neuropeptide melanin concentrating hormone (MCH). We then showed that bilateral injections in the LH of two inhibitory compounds, clonidine (an α-2 adrenergic agonist) and muscimol (a GABAa agonist) induce an inhibition of PS. Furthermore, after muscimol injections in the LH, the VLPAG/dDpMe contained a large number of activated neurons, mostly GABAergic, and projecting to the SLD. Altogether, our results indicate for the first time that the activation of a population of LH neurons, in part MCH containing, is necessary for PS to occur. Furthermore, our results strongly suggest that these neurons trigger PS by means of their inhibitory projection to the PS-off GABAergic neurons located in the VLPAG/dDpMe.